Presentation - Editors (Farol, 2024)
In this thirtieth issue of Farol, we address a diversity of practices that interconnect art, education, and culture. The articles presented discuss topics ranging from creative processes to issues of decolonization and accessibility, revealing the complexity and richness of the interactions between these fields. The thematic section of this issue was organized by Larissa Zanin and Adriana Magro, with the three decades of the Capixaba Seminar on Art Education as its theme, with discussions and proposals that cross methods and epistemologies of art education.